Homeopathic Medicines in Second Wave of COVID-19: Prognostic Factor Research - Manchanda, Raj Kumar; Miglani, Anjali; Chakraborty, Moumita; Kalsi, Amrit; Meena, Baljeet Singh; Kaur, Prabhjeet; Saini, Beenu; Arora, Amit; Nagrath, Cheshta; Kannoth, Jithesh Thavarayil; Kudiyarasu, Ram Kumar; Vardaan, Rahul; Brahmachari, Smita; Kumar, Yogesh; Amitav, B.; Konthembath, Pramod; Gupta, Ankit; Lolugu, Suresh Kumar; Goel, Pawan; Arora, Shelly; Balan, Shirin; Sharma, Kavita; Chawla, Anu; Ray, Malaya Kumar; Jacob, Vineetha Susan; Kumar, Udesh; Verma, Vikas Kumar; Singh, Rahul Kumar; Saha, Abishes; Ghuliani, Manjula; Kaur, Paramjeet; Gora, Shruti; Gupta, Meeta; Sharma, Brender; Rutten, Lex (Homeopathy, 2022)
Background The clinical profile and course of COVID-19 evolved perilously in a second wave, leading to the use of various treatment modalities that included homeopathy. This prognostic factor research (PFR) study aimed to identify clinically useful homeopathic medicines in this second wave.Methods This was a retrospective, multi-centred observational study performed from March 2021 to May 2021 on confirmed COVID-19 cases who were either in home isolation or at COVID Care Centres in Delhi, India. The data were collected from integrated COVID Care Centres where homeopathic medicines were prescribed along with conventional treatment. Only those cases that met a set of selection criteria were considered for analysis. The likelihood ratio (LR) was calculated for the frequently occurring symptoms of the prescribed medicines. An LR of 1.3 or greater was considered meaningful.Results Out of 769 confirmed COVID-19 cases reported, 514 cases were selected for analysis, including 467 in home isolation. The most common complaints were cough, fever, myalgia, sore throat, loss of taste and/or smell, and anxiety. Most cases improved and there was no adverse reaction. Certain new symptoms, e.g., headache, dryness of mouth and conjunctivitis, were also seen. Thirty-nine medicines were prescribed, the most frequent being Bryonia alba followed by Arsenicum album, Pulsatilla nigricans, Belladonna, Gelsemium sempervirens, Hepar sulphuris, Phosphorus, Rhus toxicodendron and Mercurius solubilis. By calculating LR, the prescribing indications of these nine medicines were ascertained.Conclusion Add-on use of homeopathic medicines has shown encouraging results in the second wave of COVID-19 in integrated care facilities. Further COVID-related research is required to be undertaken on the most commonly prescribed medicines.
Keywords: COVID-19; second wave; homeopathy; prognostic factor research; likelihood ratio